Pengaruh Literasi Media Internet Terhadap Kemampuan Berpikir Kritis Siswa Dalam Pembelajaran Ilmu Pengetahuan Sosial Di Era Covid-19 - Rifqi Nasrikin; Kokom Komalasari; Mamat Ruhimat (Jurnal Civic Hukum, 2023)
This study aims to provide an overview of internet media literacy in social studies learning among state junior high school students in the city of Bandung, an overview of students' critical thinking skills in social studies learning in public junior high schools in the city of Bandung, and the effect of internet media literacy on students' critical thinking skills in social studies learning in Junior High School in the City of Bandung. The research method used in this study is a survey. The data collection tool used in this study was a questionnaire, which was carried out by distributing a set list of questions or written statements to respondents to answer. The results of the study show that the effect of internet media literacy on students' critical thinking skills in social studies learning is 45%. This percentage is relatively large, a small part of students' critical thinking abilities in social studies learning is influenced by internet media literacy variables. So it can be said that internet media literacy has such an effect on students' critical thinking skills, especially in social studies learning for Bandung City Middle School students.